2020
DOI: 10.1038/s41372-020-0622-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patent ductus arteriosus on coronary artery blood flow in premature infants: a prospective observational pilot study

Abstract: Objective To compare coronary flows between premature infants with and without hemodynamically significant patent ductus arteriosus (hsPDA) and to determine if coronary flow is influenced by medical PDA treatment.Design Prospective, observational pilot study. Forty-three infants <32 weeks gestation underwent echocardiography when routinely indicated. Study group included infants with hsPDA requiring treatment. Comparison groups included infants with nonsignificant PDA and infants without PDA. Results The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…We may hypothesize that the difference in hs cTnT levels is a result of the higher oxygen need of stressed and stretched myocytes caused by hsPDA. Our results are supported by, Asrani et al, who documented that the mean of hs cTnT amounts were significantly increased in cases had hsPDA than cases had not hsPDA (p = 0.01) [16] . In the same context, the association between hs cTnT levels and respiratory failure in new-borns was studied by Tüfekci et al, 113 healthy new-borns and 93 new-borns with noncardiac respiratory failure, were assessed.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We may hypothesize that the difference in hs cTnT levels is a result of the higher oxygen need of stressed and stretched myocytes caused by hsPDA. Our results are supported by, Asrani et al, who documented that the mean of hs cTnT amounts were significantly increased in cases had hsPDA than cases had not hsPDA (p = 0.01) [16] . In the same context, the association between hs cTnT levels and respiratory failure in new-borns was studied by Tüfekci et al, 113 healthy new-borns and 93 new-borns with noncardiac respiratory failure, were assessed.…”
Section: Resultssupporting
confidence: 89%
“…Our results are compatible with Asrani et al, who reported that average PDA diameter in infants was higher in infants with hsPDA in the pre-treatment than with the diameter in the post-treatment (p = 0.0007). The average LA:AO ratio was higher in infants with hsPDA in the pretreatment than with the post-treatment group (p = 0.06) [16] . In the present study, the need for oxygen support was significantly increased in cases had hsPDA than cases had not hsPDA (P value=0.001), the duration of oxygen support and hospital stay was significantly longer in patients with hsPDA than patients without hsPDA (P value=0.013, 0.001).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…I read with interest the article by Vaisbourd et al [1] published in the recent issue of Journal of Perinatology. They described decrease in coronary artery flow and higher troponin values suggesting it as a "steal effect" in association with patent ductus arteriosus (PDA).…”
Section: To the Editormentioning
confidence: 99%
“…One of the important aspects of hemodynamic disturbance in hsPDA is the “diastolic run-off” that leads to attenuated blood flow to various peripheral organs ( 58 ). Oxygen delivery to tissues depends on blood flow and oxygen content which is reduced in these circumstances resulting in decreased regional oxygen saturation (RSO 2 ) in multiple organs particularly cerebral (cRSO 2 ), renal (rRSO 2 ), and splanchnic beds (sRSO 2 ) necessitating physiological increase in fractional tissue oxygen extraction (FTOE) to maintain tissue oxygen requirement in premature neonates.…”
Section: Introductionmentioning
confidence: 99%